Activation Cross Section Measurement of the (n,2n) Reaction on 203Tl - Diakaki Μ.; Vlastou R.; Patas S.; Chasapoglou S.; Kokkoris M.; Alamanos G.; Frantzis C.; Axiotis M.; Harissopulos S.; Lagoyannis A. (EPJ Web of Conferences, 2023)
The aim of the present work was to study the cross-section of the (n,2n) reaction on 203Tl, by irradiating a natural TlCl pellet target with monoenergetic neutron beams at 16.4, 18.9 and 19.3 MeV. The cross section of the 203Tl(n,2n)202Tl reaction was measured via the activation method, with respect to the 197Au(n,2n)196Au and 27Al(n,α)24Na reference reactions. At the same time, the 203Tl(n,3n)201Tl was also measured at 18.9 and 19.3 MeV. The monoenergetic neutron beams were generated at the 5.5 MV Tandem accelerator of NCSR “Demokritos”, using the 3H(d,n)4He reaction. In addition, theoretical calculations with the EMPIRE code have been performed, in order to find a suitable model for the description of the experimental data of the present work along with the data from literature.